Investigate the effect of process parameters of magnetic inductively assisted spark plasma sintering (SPS) of iron oxide (Fe3O4) on microstructure behaviour - Part i - Mohammed, H.G. (Elsevier Ltd, 2021)
A new magnetically assisted spark plasma sintering as a novel method of adding a continuous intensive magnetic field during the sintering process was briefly introduced as an alternative method of traditional SPS in which the sintering process passed through several processes started with jet milling, aligning, densifying, and then ended up with sintering during the production of a material with excellent magnetic, electrical, and mechanical properties. Furthermore, the use of an external magnetic field parallel with the sintering process leads to a shortening of these processes in addition to driving the molten metal in a certain way for grain refinement and grain re-orientated, resulted in the reduction of porosities and cavities. In this paper (Part I) Iron oxide (Fe3O4) nanopowder has been characterized to study the sintering process's effect on microstructure behavior using FESEM, XRD, XPS, and VSM. Based on the results obtained, Fe3O4has cubic shaped particles with an average size of 100-200nm, and the indexed peaks are (1 1 1), (2 2 0), (3 1 1), (2 2 2), (4 0 0), (4 2 2), (5 1 1), and (4 0 0), which confirmed with the standard. Â© 2021 Elsevier Ltd. All rights reserved.